The role of green marketing towards purchase intention among Malaysian customers - Sathiswaran Uthamaputhran; Azlinda Shazneem Md Shuaib; Nurul Hasliana Hamsani (2014)
This study investigates the relationship between green marketing strategies and customer purchase intention towards green products. The objective of the study is to examine the effectiveness of perceived green marketing in customers’ purchase intention in Malaysia. The finding has been supported by the Elaboration Likelihood Model (ELM) and the Affect-ReasonInvolvement model (ARI). For this purpose, 500 questionnaires were distributed to customers in Giant and Econ Save. However, only 200 questionnaires were received without response bias. Thus, the overall response rate was 40%. This study was analyzed using the Structural Equation Model that comprised of factor loading analysis, discriminant analysis, and Goodness Model Fit. Findings of this study prove that there is a positive relationship between green marketing strategies and customers’ purchase intention towards green products. Overall, these variables are important elements in influencing customers in making a purchase decision